Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas VII B MTs Hasyim Asy’ari pada Materi Operasi Hitung Aljabar Melalui Model Pembelajaran Drill and Practice - Tri Wahyuni (Universitas Mercu Buana Yogyakarta, 2025)
Based on the results of observations and discussions with mathematics teachers and students, it is known that the low ability of students in problem solving is due to the lack of students practicing working on mathematics problems, which has an impact on student learning outcomes. The drill and practice method is one of the learning methods that emphasizes the amount of practice. The purpose of this study is to improve students' mathematical problem-solving abilities through the application of the drill and practice learning method. This study uses Classroom Action Research (CAR) in two cycles. The subjects of this study were 22 students of class VII B MTs Hasyim Asy'ari in the 2024/2025 academic year. The object of the study was the overall learning outcomes by applying the drill and practice method to improve students' mathematical problem-solving abilities. Data collection techniques used documentation and tests. The data obtained were analyzed using descriptive statistics consisting of mean and percentage. The results showed that there was an increase in the average percentage criteria for the final score of students' mathematical problem-solving abilities with criteria of less in cycle I togood in cycle II.